Gejala Pergeseran Minat Berwirausaha Anak Muda di Yogyakarta Ditinjau dari Aspek Kreativitas dan Motivasi - Wisnu Hadi; Atun Yulianto (Media Wisata, 2015)
This study aims to determine the effect of the symptoms of the entrepreneurial aspects of the shift of interest in terms of the aspect of creativity of young people, the interest in entrepreneurship in young people aspects of motivation and interest entrepreneurship together with aspects of creativity and motivation of young people in the region involves Yogyakarta. Research 100 young people as respondents who have business in the area of Yogyakarta. Sampling was done by proportional random sampling technique with 75 young people. This study uses a design ex-post facto. Data were collected using questionnaires and documentation. Data were analyzed using correlation analysis. Base on these results it can be concluded that: first, there is the contribution of an interest in entrepreneurship with creative aspects of youth entrepreneurship in the region of Yogyakarta, the second is the contribution of an interest in entrepreneurship with motivational aspects of entrepreneurship, the third is the collective contribution of common interest in entrepreneurship with aspects of creativity and motivation of youth entrepreneurship in the region of Yogyakarta.